Effects of inlet/outlet locations and influent temperature on hydraulic disinfection efficiency in contact tanks - Zhang, Yishu, author; Venayagamoorthy, S. Karan, advisor; Ramirez, Jorge A., committee member; Prasad, Ashok, committee member (Colorado State University. Libraries, 2017)
This study focuses on understanding the effect of inlet/outlet locations and influent temperature on hydraulic disinfection efficiency of drinking water contact tanks for small systems. Computational fluid dynamics (CFD) simulations of flow and scalar transport in a concrete rectangular tank with three inlet/outlet location configurations were performed. The temperature of the influent into the system was varied in the second part of this study in order explore the effects of temperature gradients on the flow and scalar transport. Hydraulic disinfection efficiencies were computed through the use of residence time distribution (RTD) curves obtained from the CFD simulations and the baffling factor (BF). The physical tank that was used for all tracer tests is located at the Hydraulics Lab at Colorado State University's Engineering Research Center (ERC) in Fort Collins. The rectangular concrete tank was initially constructed with a bottom inlet and top outlet configuration and has a total volume of 1500 gallons. After the CFD simulation results were validated using tracer tests, two principle objectives were investigated using CFD simulations. First, the effect of inlet/outlet locations and their respective sizes were investigated. For a given constant temperature for both the inflow and ambient water in the tank, three inlet/outlet location combinations (i.e. bottom inlet-bottom outlet, bottom inlet-top outlet, and top inlet-bottom outlet) with two different outlet sizes (i.e. 2-in.-diameter and 4-in.-diameter) were modeled using 15 CFD simulations. Both baffled and un-baffled tanks were modeled. The resultsshow that a small modification of the outlet pipe diameter results in minor changes in the baffling factor and hydraulic disinfection efficiency. All adjusted un-baffled tanks (i.e. with the three different inlet/outlet configurations) did not yield any satisfactory disinfection performance due to the severe short circuiting that occurs in the tank. The main finding is that for baffled tanks, the top inlet-bottom outlet configuration performed the best and increased baffling factor by over 30% relative to the bottom inlet-bottom outlet configuration for the baffled tank which is commonly found in praxis. Second, the effect of buoyancy that can occur in disinfection tanks due to drastic temperature differences between the inflow and the ambient water in the contact tank was investigated. Only negatively buoyant conditions were studied in this research. Temperature differences of 0°C, 5°C, 10°C, and 15°C were created by injecting cold inflow to the baffled tanks under two conditions namely: (i) no heat flux condition and (ii) constant wall condition. For the first condition, it was assumed that no heat exchange between tank (and baffle) walls and fluid occurs; while for the second condition, the wall temperature was held constant at 20°C. Both conditions were simulated at different flow rates to capture flow regimes ranging from laminar to turbulent. It was found that the baffling factor varied significantly between laminar, transitional, and turbulent flows. The best hydraulic disinfection efficiency was achieved when the flow was laminar. For no heat flux condition, the effects of the buoyancy increased baffling factor by 57% compared to the base case with no temperature difference. On the other hand, for turbulent flow conditions with a strong temperature difference, the baffling factor reduced by 49% compared to the base case. The constant wall temperature condition produced similar results, but with a smaller change in baffling factor. From a hydrodynamic analysis of the flow fields obtained from CFD simulations, it was concluded that buoyancy could either increase hydraulic disinfection efficiency or decrease it, depending on the flow regime. Hence, care should be exercised to avoid flows in transitional to turbulent regimes because the negative buoyancy could decrease the baffling factor and lead to inadequate microbial deactivation.
Keywords: drinking water treatment; CFD; hydraulic disinfection efficiency